Implementasi Model Rapid Application Development untuk Pengembangan Pembelajaran Tajwid Al-Qur'an: Implementation of Rapid Application Development Model for the Development of Qur'an Tajweed Learning - Rice Novita (Institut Riset dan Publikasi Indonesia, 2023)
Shaykh Manna Al-Qahthan said that the Qur'an is the message of Allah SWT for all humankind. As a country with a majority Muslim population, 87.18% based on statistical data at the end of 2010 from the Central Statistics Agency. Data from research conducted by the Institute of Al-Qur'an Sciences in 2017 noted that around 65% of Indonesian Muslim communities are illiterate in the Qur'an. Learning tajweed Al-Qur'an by taking classes directly usually will take longer to master one material because it is carried out once a week. Information Technology can be utilized in this problem. Android-based application is one of them. The focus of this research is build a mobile application for learning Al-Qur'an recitation with the Nurul Bayan method using the Rapid Application Development system method. The results of the Blackbox test calculation on the Tajweed Learning Application are 100% and the results of the UAT test are. Based on the results of testing using the Blackbox Testing and User Acceptance Test methods, Android-based Tajweed Learning Applications can assist users in learning the basic theory of Al-Qur'an recitation with the Nurul Bayan method.